A escala de Waterlow na úlcera por pressão em pessoas com lesão medular : uma tecnologia assistencial de enfermagem - Studart, Rita Mônica Borges (2009)
The application of assistant technology in nursing professional practice to evaluate pressure ulcers in spinal cord injured patients must be an holistic approach, involving a multiprofessional team. This study purposed to evaluate the risk factors linked to pressure ulcers in persons hospitalized due to spinal cord injury, using the Waterlow scale. Transversal study, with 60 patients from a municipal public emergency hospital of Fortaleza, in which data were collected between May 2008 and October 2008. The population was constituted by patients interned in Infirmaries: Neurosurgery, UTI, Traumatology and General Surgery with spinal cord injury diagnosis. Two instruments were used for collecting the data, containing identification data and risk factors, elaborated by bibliographical consulting using the Waterlow scale. Data were collected at two stages: the first one the interview and physical exam in patients at the primary 72h of incoming, in the second one at 10 days of incoming. Data were summarized by the software Excel, based on plans, and the statistical analysis was made by SPSS program 13.0 version. Statistical test were performed to data association analysis: Kolmogorov-Smirnov Test, Pearson’s Correlation Coefficient and Spearmen’s Correlation Coefficient. All ethical recommendations were followed during the research stages. In this study, most of all patients affected by pressure ulcers were male, between 18 and 33 years old, with an age average of 37,12 years, coming from the capital urban area, with salary average and scholar status low. The application of the Waterlow scale, performed in this study, demonstrated efficacy and sensibility to evaluate risk factors to pressure ulcers in spinal cord injured hospitalized persons. Supported by the results, it is believed that in the first moment of the evaluation using the Waterlow scale the Body Mass Index should be dismissed, due to the difficulty of measuring it. Besides, it was revealed that spinal cord injured patient has a great risk to developing pressure ulcers, not depending on Body Mass Index. The most significant risk factor to pressure ulcers in that patient was the physical mobility damaged linked to the time of hospitalization. The presence of a companion was other important evidence, so that all of the 19 patients that not developed pressure ulcers were accompanied. It was also showed that 90% of the patients did not receive any kind of information before pressure ulcer occurrence and that only 31% received information after the pressure ulcer occurrence. This study permitted to know deeply the most important risks to pressure ulcers in spinal cord injured patients using the Waterlow scale